Identification of MSX1 mutation in Malaysian hypodontia family - Muhamad Zamil, Nabilah; Mohamed Yussof, Nor Aini; Ardini, Yunita Dewi; Lestari, Widya (Atlantis Press, 2018)
Hypodontia is defined as the absence of one to six teeth. There is high prevalence of hypodontia recorded in Malaysia (2.8%). This study aimed to identify any mutation of MSX1 in Malaysian family with hypodontia and its clinical finding. We re-examined 4 individuals from a family of the previous PAX9 study. Orthophantomogram (OPG) and intraoral photos were re-assessed. Saliva was collected for genetic analysis. Direct sequencing was done on exons 1 and 2 of MSX1. 2 out of 4 members (1A and 1D) in the family have anterior hypodontia. Point mutation on exon1 of MSX1 (c.731G>A) was observed in 1A (father) with missing 13 and 23 and 1C (carrier-son). c.732G>A was found on exon1 of MSX1 of his daughter (1D) with missing 32.MSX1 mutation is involved in the occurrence of hypodontia in patient.